Determination of potency and paraspecific effects of Androctonus crassicauda (Olivier, 1807) antivenom against Mesobuthus gibbosus (Brullé, 1832) venom (Scorpiones: Buthidae) - Ozkan,O. (2007)
Scorpion envenomation remains a real health problem in many countries. In scorpionism cases, it is often recommended that patients be treated with species-specific antivenom. Androctonus crassicauda venom has been used as antigen for antivenom production in Turkey, where this antivenom, called Turkish antivenom, has also been effective in the treatment of envenomation caused by species other than A. crassicauda. The present study aimed at determining the paraspecific effects and potency of the Turkish antivenom against Mesobuthus gibbosus (Brullé, 1832) venom. To assess the venom toxicity and the antivenom efficacy, we determined the Minimum Lethal Dose (MLD) and the Minimum Effective Dose (MED) instead of LD50 and ED50, respectively. Androctonus crassicauda antivenom was capable of neutralizing M. gibbosus venom (20 MLD). This was the first study indicating that A. crassicauda antivenom can be used for the treatment of Mesobuthus gibbosus stings, especially in Aegean Region, Turkey.